Absence of the interthalamic adhesion (ITA) as a neuroanatomical association or risk factor for neuropsychiatric disorders: A systemic review and meta-analysis - Adil Asghar; Ravi K. Narayan; Pankaj Kumar; Kumar S. Ravi; R. Shane Tubbs; Apurba Patra; Shagufta Naaz (Indian Journal of Psychiatry)
Background: This study aimed to provide an up-to-date account of the frequency of “the absence of interthalamic adhesion (AITA) as a risk factor or association” in healthy subjects and neuropsychiatric patients. Owing to the increased interest in the contribution of ITA to neurological function in previous literature, a meta-analysis of its frequency and sex dependency is required. Aim: This study aimed to study whether the AITA is associated with neuropsychiatric disorders. Settings and Design: This study is a meta-analysis and systemic review. Methods and Material: Literature searches were conducted in PubMed, Web of Science, and Google Scholar using the keywords “interthalamic adhesion,” “massa intermedia,” “adhesio interthalamica,” and “adhesion” along with the Boolean operators (OR, AND, and NOT). Three reviewers independently assessed the abstracts and full texts for validation based on the inclusion criteria. The meta-analysis was performed using Microsoft Excel 2019 for descriptive studies and RevMan 5.2 for comparative studies. Results: The incidence of absent ITA was 15.3% in healthy subjects and 28.76% in neuropsychiatric subjects. The relative probability of AITA was 2.30 [95% confidence interval (CI), 1.96–2.70] in neuropsychiatric illness. Healthy men were 1.91 times more likely, and men with neuropsychiatric disorders were 1.82 times more likely to have absent ITA than women. Conclusions and Relevance: In this study, a consistent association of AITA with psychiatric disorders was observed, rendering the condition to be treated as an associated risk factor affecting the function of the habenula nuclear complex via the stria medullaris thalami. A cohort or longitudinal study is needed to compare the incidence of psychiatric disorders in individuals with or without ITA and to calculate the attributed risk.